Drafting Effect in Cycling: Investigation by Wind Tunnel Tests. (2016) - Belloli, Marco; Giappino, Stefano; Robustelli, Fabio; Somaschini, Claudio
Abstract: Cyclists travelling in groups experience a significant reduction in the wind resistance and those behind consume less energy due to the shielding effect of the front cyclist. We investigated drafting effects by wind tunnel tests realizing a test set-up with two cyclists pedalling at different longitudinal distance. Drag reduction effects on both the leading and the trailing cyclist are confirmed. The presence of lateral wind is also investigated showing a significant reduction of the drafting effect also for light winds.